2007
DOI: 10.1159/000099332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peritoneal Transport and Membrane Status in Peritoneal Dialysis: Focus on Incident Fast Transporters

Abstract: Background/Aim: The determinants of baseline fast solute transport are still unclear. We prospectively investigated the relationship of peritoneal solute transport with markers of inflammation, angiogenesis, and membrane status, with a focus on fast transporters. Methods: Seventy-one incident peritoneal dialysis patients were assessed with baseline and annual peritoneal equilibration tests, using a 3.86% glucose dialysis solution. Residual renal function and markers of inflammation, including systemic and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 55 publications
5
32
3
1
Order By: Relevance
“…This result in accordance with those from published longitudinal studies [15][16][17]. This downward trend with time suggests a decrease in mesothelial cell mass.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result in accordance with those from published longitudinal studies [15][16][17]. This downward trend with time suggests a decrease in mesothelial cell mass.…”
Section: Discussionsupporting
confidence: 92%
“…Dialysate CA125 levels have been shown in some studies to decrease in long-term PD treatment [13][14][15][16], but there are currently limited longitudinal data on children undergoing long-term PD [17]. The aim of the study reported here was to evaluate changes in dCA125 levels in peritoneal effluent over time and to analyze relationships between dCA125 and PGE in children treated with long-term PD.…”
Section: Introductionmentioning
confidence: 99%
“…Although this has been recently questioned [31] , the finding of low levels of effluent CA125 in long-term PD, notably with UFF make it worthwhile to be routinely measured, in order to clarify its predictive value. It was not the purpose of this study to investigate the relationship between mesothelial cell mass and peritoneal transport: an indirect role has recently been suggested but this seems to vary in short-and long-term PD, possibly mediated earlier by production of vasoactive factors [32][33][34] or later trough epithelial-mesenchymal transition [35] . This should be preferably investigated in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…It goes along with high effluent concentrations of CA125 [19] and the production of biomarkers that are partly vasoactive [20]. Inflammation may [21] or may not be present [22]. Therefore, the regulation of the peritoneal circulation in fast transporters is different from that of the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%